Port perspectives in a changing climate: strategies for enduring impact - Tugi, Astina; Mohamad Abdullah, Nazirah; Md Din, Ami Hassan; Md Said, Najhan; Ismail, Badrul Hisham (SINERGI, 2025)
More than 50% of the world's trade happens via seaborne line. The sustainability of the ports is crucial as it boosts economic growth. However, climate change and its effects have disturbed the port's activities. This paper highlighted the possibility of climate change effects threatening some ports worldwide. A systematic literature review has been conducted, and 11 resources have been used to summarize their impact on port activities. The climate change effects encountered by the ports and their authorities' adaptation measures are underlined. Ports worldwide are considered. As a result, sea level rise (SLR), storm surges, and flooding are some threats that can affect port activities. Adaptation and mitigation plans can be more successfully implemented with excellent knowledge of the factors leading to increased exposure. From the port expansion to creating a new location of ports, the other mitigation and adaptation plan towards the sustainable ports is by providing an accurate topographic map, a good simulation software, and good resilience infrastructures and adaptation framework. The related ports have suggested and implemented adaptation and mitigation approaches to resolve the problem and sustain their ports and harbour activities. Adaptation and mitigation measures taken will respond to the effects of climate change.